Diet and ecomorphology of Leporinus reticulatus (Characiformes: Anostomidae) from the upper Rio Juruena, MT, Brazil: ontogenetic shifts related to the feeding ecology - Machado-Evangelista, Mariana [UNESP]; EsguÍcero, André Luiz Henríques; Arcifa, Marlene Sofia; Pereira, Thiago Nilton Alves (Instituto Nacional de Pesquisas da Amazônia, 2015)
The conservation of diverse and well-distributed fish taxa, as the genus Leporinus, relies intrinsically on the knowledge of the ecological attributes of its representatives. Aiming to increase this knowledge, studies on diet and ecomorphology are ideal to provide important information about species ecology. Thus, this study aimed to analyze aspects of feeding ecology of L. reticulatus, from the upper Rio Juruena, Mato Grosso State, Brazil. The diet of specimens in different ontogenetic stages was compared, as well as their teeth morphology and ecomorphological attributes. Leporinus reticulatus presented omnivorous diet, with higher consumption of invertebrates by smaller specimens (younger ones), and gradual introduction of plant items in larger specimens (older ones). The items consumed by the individuals and the ecomorphological attributes indicated that the species is generalist and opportunistic, besides its association with the river bottom, evidencing a benthic feeding behavior. This species presents a gradual ontogenetic modification in teeth shape and mouth positioning, ranging from a terminal mouth with tricuspid teeth, in smaller specimens, to an inferior mouth with spatula shaped teeth with no cusps, in larger specimens.The ecomorphological attributes indicate an increasing swimming efficiency, and ability for performing vertical displacements, along the ontogenetic development, which in addition to the morphological ontogenetic alterations in the buccal apparatus, contributes to a better ability to explore another niches.

A conservação de táxons de peixes de grande diversidade e amplamente distribuídos, como o gênero Leporinus, depende intrinsicamente do conhecimento de atributos ecológicos de seus representantes. Objetivando o aumento deste conhecimento, estudos que abordam a dieta e a ecomorfologia são ideais para prover informações importantes sobre a ecologia de espécies. Assim, este trabalho teve como objetivo analisar aspectos da ecologia alimentar de L. reticulatus originários do alto Rio Juruena, estado do Mato Grosso, Brasil. Foi comparada a dieta de espécimes em diferentes estágios ontogenéticos, assim como a morfologia dos dentes e atributos ecomorfológicos. Leporinus reticulatus apresentou dieta onívora, com maior consumo de invertebrados pelos espécimes de menor porte (mais jovens), e introdução gradual de itens vegetais por espécimes de maior porte (mais velhos). Os itens consumidos pelos indivíduos e os atributos ecomorfológicos indicaram que esta espécie é generalista e oportunista, além de sua associação com o fundo do rio, evidenciando um comportamento alimentar bentônico. Esta espécie apresenta modificação ontogenética gradual no formato dos dentes e posição da boca, variando de uma boca terminal e dentes tricúspides, em espécimes menores, a uma boca inferior e dentes em forma de espátula sem cúspides, em espécimes maiores. Os atributos ecomorfológicos indicaram um crescente aumento na eficiência natatória, e na habilidade de realizar deslocamentos verticais, ao longo do desenvolvimento ontogenético, o que, em conjunto às alterações morfológicas ontogenéticas no aparato bucal, contribuem para uma melhor habilidade em explorar outros nichos.
Dieta e ecomorfologia de Leporinus reticulatus (Characiformes: Anostomidae) do alto Rio Juruena, MT, Brasil: alterações ontogenéticas relacionadas à ecologia alimentar
Keywords: Neotropical ichthyofauna; Freshwater fish; Trophic ecology; Ontogenetic morphological variation; Ictiofauna Neotropical; Peixes dulcícolas; Ecologia trófica; Variação ontogenética morfológica